KAJIAN SUPERPARASIT DAN PREFERENSI INANG BENALU Viscum articulation Burm. f. (Viscaceae) DIKEBUN RAYA PURWODADI DAN CIBODAS - Sunaryo Sunaryo (BERITA BIOLOGI, 2010)
Superparasite is a parasitic plant that lives on other parasitic plant. Viscum articulatum Burm. f. (Viscaceae) is a parasitic species of mistletoe that grows on other parasitic species of mistletoes, thus a superparasite. In Purwodadi Botanic Gardens-LIPI, East Java V. articulatum grows on Dendrophthoe pentandra and Macrosolen tetragonus. In Cibodas Botanic Gardens-LIPI, West Java it grows on D. pentandra and M. cochinchinensis. Dendrophthoe pentandra is the most infected species.The infected mistletoes are regarded as the first stage hosts.The living collections at both Botanic Gardens parasited by the three mistletoes are regarded as the second stages host.Investation preference for first and second host stages is studied in this research.